Optimalisasi Manajemen Kinerja Dalam Meningkatkan Kompetensi Professional Guru: Strategi Dan Tantangan - Hakim, Lukman (Civiliza Publishing, Indonesia., 2023)
The main target in preparing this work is to find out effective performance management strategies in developing teacher professional competence and the main challenges faced by teachers in implementing optimal performance management. This research uses descriptive qualitative methods to understand strategies and challenges in teacher performance management at MTs Nurul Jadid Probolinggo. Data was obtained through interviews, observations and document analysis, then analyzed to identify effective strategies and challenges that need to be overcome. The results of this work are a) At MTs Nurul Jadid Probolinggo, a teacher performance management strategy based on Total Quality Management (TQM) has been implemented, including the development of individual lesson plans, training, and a quality-oriented approach, which is supported by the use of Bloom's taxonomy and teacher professionalism. The impact is increased teacher competence and better student achievement. b) The main challenges for teachers at MTs Nurul Jadid Probolinggo in implementing optimal performance management include limited resources, lack of understanding, and low motivation. Using Total Quality Management (TQM) and Bloom's taxonomy, as well as increasing professionalism and support from schools, can help teachers overcome these challenges and improve the quality of teaching.